Calcium, channels, intracellular signaling and autoimmunity (2014)
Calcium (Ca2+) is an important cation able to function as a second messenger in different cells of the immune system, particularly in B and T lymphocytes, macrophages, and mastocytes, among others. Recent discoveries related to the entry of Ca2+ through the store-operated calcium entry (SOCE) have opened a new investigation area about the cell destiny regulated by Ca2+ especially in B and T lymphocytes. SOCE acts through calcium-release-activated calcium (CRAC) channels. The function of CRAC depends upon two recently discovered regulators: the Ca2+ sensor in the endoplasmic reticulum or stromal interaction molecule (STIM-1) and one subunit of CRAC channels called Orai1. This review focuses on the role of Ca2+ signals in B and T lymphocytes functions, the signaling pathways leading to Ca2+ influx, and the relationship between Ca2+ signals and autoimmune diseases.